ANALISIS KOMUNIKASI DAKWAH MELALUI ANIMASI DI TIKTOK: STUDI KASUS PADA AKUN @TAARTS_TOK - Amalia Khairul Mafaza; Fathimah Zahro Al Ghoziyah; Ludfiya Nurcahyani Oktafiya; Yasmina Bilqis Muharomah (As-Sulthan Journal of Education, 2025)
This study aims to analyze Islamic preaching communication through animation on the TikTok platform, using a case study of the @taarts_tok account. The research questions include: how is audiovisual Islamic preaching communicated through animation on this account, and how do audiences respond to such content? This research uses a descriptive qualitative approach with a case study method, employing content analysis techniques on selected short animation videos through purposive sampling. The findings reveal that @taarts_tok utilizes persuasive, educative, and reflective preaching strategies by combining visual elements, voice-over narration, text, and background music. The content is presented in a minimalist and contemplative style, featuring symbolic visuals and emotional narratives that resonate strongly with Generation Z. Audience responses in the comment section reflect deep emotional and spiritual engagement. This research contributes to the development of Islamic communication and broadcasting studies, particularly in the context of digital media.